Unraveling the link between family of origin and parental responsiveness toward own child - Anikiej-Wiczenbach, Paulina; Kaźmierczak, Maria (Frontiers in Psychiatry, 2023)
This study investigates the influence of family of origin on parental responsiveness toward own child, taking into account gender differences. A total of 110 triads of mothers, fathers, and their first child aged 6–10 months participated in the standardized Free Play procedure. Parental responsiveness was assessed through observational measures (using Ainsworth procedure) and self-reported scales (Parental Responsiveness Scale). Results revealed correlations between objectively assessed responsiveness and self-reported parental styles in the family of origin, separately for mothers and fathers. Among mothers having daughters, parental sensitivity (an important aspect of observationally measured responsiveness) was positively correlated with having had a liberal loving mother and a negative correlation with an autocratic mother. Cooperation (another aspect of observationally measured responsiveness) was correlated positively with having had a liberal loving mother. Meanwhile, having a liberal unloving mother predicted lover sensitivity and cooperation. Similar correlations were not observed for mothers having sons. Among fathers having daughters, both aspects of observed responsiveness were positively correlated with having had a democratic father and negatively with autocratic or liberal unloving parents. Moreover, having a liberal unloving father and autocratic mother predicted their lower responsiveness toward daughters. These findings highlight the role of family dynamics in shaping parental responsiveness and emphasize the importance of understanding these dynamics in promoting responsive parenting.